Konstruksi Neo Sufisme oleh Jhon O Voll - Moh. Ali Akbar Nafis (4, 2025)
The revival and renewal of Islam in the 18th to early 19th centuries became a significant momentum that attracted serious attention from Western academics. This attention was particularly focused on the role of Sufi brotherhoods, which not only functioned as spiritual communities but also emerged as an active social force in responding to and resisting colonialism. This dynamic then gave birth to an academic construct known as neo-Sufism, which is understood as a new form of Sufism with a more open and contextual social and political orientation. This study aims to review the historical construction of neo-Sufism as it developed in Western academic discourse, while also critically analyzing John O. Voll's thoughts in responding to and revising the previous Orientalist construction of neo-Sufism. In addition, this study also attempts to describe the characteristics of neo-Sufism, particularly in relation to its adaptive capacity to the demands of modernity. The method used is library research, with the primary sources being the works of John O. Voll and Nehemia Levtzion, and supported by various relevant secondary literature to enrich the analysis. The research findings show that the emergence of the concept of neo-Sufism is inextricably linked to Western academics' attention to the rise of Islam in North Africa, where Sufi movements play a significant role in the socio-religious and political dynamics of society. John O. Voll emphasizes the importance of reexamining the concept of neo-Sufism that has developed over time, as it is often understood simplistically and tends to be associated with radicalism. According to Voll, neo-Sufism is actually a form of Sufism's adaptation to modernity, reflected in a spirit of internationalism, increased political mobility of civil society, and a strong orientation towards social service and empowerment. Abstrak Peristiwa kebangkitan dan pembaharuan Islam pada abad ke-18 hingga awal abad ke-19 menjadi salah satu momentum penting yang menarik perhatian serius para akademisi Barat. Perhatian tersebut terutama tertuju pada peran persaudaraan sufi yang tidak hanya berfungsi sebagai komunitas spiritual, tetapi juga tampil sebagai kekuatan sosial yang aktif dalam merespons dan melawan kolonialisme. Dinamika ini kemudian melahirkan sebuah konstruksi akademik yang dikenal dengan istilah neo-sufisme, yang dipahami sebagai bentuk baru tasawuf dengan orientasi sosial dan politik yang lebih terbuka serta kontekstual. Kajian ini bertujuan untuk mengulas konstruksi historis neo-sufisme sebagaimana berkembang dalam wacana akademisi Barat, sekaligus menganalisis secara kritis pemikiran John O. Voll dalam menyikapi dan merevisi konstruksi neo-sufisme orientalis sebelumnya. Selain itu, penelitian ini juga berupaya mendeskripsikan karakteristik neo-sufisme, khususnya dalam kaitannya dengan kemampuan adaptifnya terhadap tuntutan modernitas. Metode yang digunakan adalah library research, dengan sumber utama berupa karya-karya John O. Voll dan Nehemia Levtzion, serta didukung oleh berbagai literatur sekunder yang relevan untuk memperkaya analisis. Hasil penelitian menunjukkan bahwa kemunculan konsep neo-sufisme tidak dapat dilepaskan dari perhatian akademisi Barat terhadap kebangkitan Islam di Afrika Utara, di mana gerakan sufi memainkan peran signifikan dalam dinamika sosial-keagamaan dan politik masyarakat. John O. Voll menekankan pentingnya pengkajian ulang terhadap konsep neo-sufisme yang selama ini berkembang, karena sering kali dipahami secara simplistik dan cenderung dikaitkan dengan radikalisme. Menurut Voll, neo-sufisme justru merupakan bentuk adaptasi tasawuf terhadap modernitas, yang tercermin dalam semangat internasionalisme, meningkatnya mobilitas politik masyarakat sipil, serta orientasi kuat pada pengabdian dan pemberdayaan sosial.